1977
DOI: 10.1002/prac.19773190215
|View full text |Cite
|
Sign up to set email alerts
|

Versuche an einer neuen Caprolactamsynthese. II [1]. Umlagerung von 3,3‐Pentamethylen‐oxaziridin in Caprolactam

Abstract: 3,3‐Pentamethylen‐oxaziridin 1 läβt sich durch Flash‐Pyrolyse bei 300 °C in Caprolactam umlagern. In Gegenwart katalytischer Mengen von Vanadinverbindungen läuft die Umlagerung bereits in siedendem Benzol oder Toluol mit Ausbeuten bis zu 95% ab. Es wird ein homolytischer Mechanismus diskutiert und durch radikalische Alkylierung von Acetylacetonaten wahrscheinlich gemacht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The conversion 311 -> 312 shown above may equally well involve β scission of the cycloalkylamino radical 315 (546). Instances of similar rearrangements are known.…”
Section: 309 310mentioning
confidence: 90%
“…The conversion 311 -> 312 shown above may equally well involve β scission of the cycloalkylamino radical 315 (546). Instances of similar rearrangements are known.…”
Section: 309 310mentioning
confidence: 90%
“…Furthermore, neither the amination product of 17 with the starting amine nor amides derived from rearrangement of 17 could be detected among the products. Oxazirane 17 is a very active amination reagent and also undergoes rearrangement to amides …”
Section: Resultsmentioning
confidence: 99%
“…The photochemical rearrangement is a valuable alternative to Schmidt and Beckmann rearrangements which usually require strongly acidic conditions, causing serious problems such as low regioselectivity of the reactions or decomposition of products.5 The corresponding thermal rearrangement of spirooxaziridines is, however, substrate-dependent and inferior to the photochemical process with respect to the efficiency and selectivity.3 Only one catalyst has been developed for the synthesis of a lactam from a spirooxaziridine. 6 We have recently reported that high valent metalloporphyrins work as a mild and characteristic Lewis-acid catalyst for the rearrangement of oxaziridines into amides.7 Therefore, we expected these metalloporphyrins could be used in the ring-expanding rearrangement of spirooxaziridines into lactams. Reported herein is a new and highly efficient transformation of Narylspirooxaziridines 1 into lactams 2 with high valent metalloporphyrins, especially manganese(ri1) tetraphenylporphyrin, Mn(tpp)Cl.…”
Section: Metalloporphyrin-catalysed Rearrangement Of Oxaziridines: An...mentioning
confidence: 99%